Silica particles and method for producing same

By integrating a quaternary ammonium salt and using supercritical fluid treatment, the silica particles' capacitance is controlled, addressing the issue of high capacitance and static electricity accumulation, enhancing their performance in applications like fillers and toners.

JP7613008B2Active Publication Date: 2025-01-15FUJIFILM BUSINESS INNOVATION CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2020106413
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-24
Filing Date
2020-06-19
Publication Date
2025-01-15
Estimated Expiration
2040-06-19

AI Technical Summary

Technical Problem

Conventional silica particles exhibit high capacitance on the particle surface, leading to increased electrical resistance and static electricity accumulation when in contact with other materials.

Method used

Incorporation of a quaternary ammonium salt into silica particles, followed by surface treatment using a supercritical fluid, to control pore distribution and reduce capacitance, along with specific mixing and baking processes to enhance the silica particles' properties.

Benefits of technology

The treated silica particles exhibit suppressed capacitance, reducing the likelihood of static electricity accumulation and electrical resistance, thereby improving their performance in applications such as fillers and toners.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007613008000001
    Figure 0007613008000001
  • Figure 0007613008000002
    Figure 0007613008000002
  • Figure 0007613008000003
    Figure 0007613008000003
Patent Text Reader

Abstract

To provide silica particles suppressed in increase in capacitance.SOLUTION: There are provided silica particles containing a quaternary ammonium salt, in which a ratio (FBEFORE / FAFTER) between a maximum value FBEFORE of the frequency of a pore diameter of 2 nm determined from a pore distribution curve by a nitrogen gas adsorption method in silica particles before cleaning and a maximum value FAFTER of the frequency of a pore diameter of 2 nm determined from a pore distribution curve by a nitrogen gas adsorption method in silica particles after cleaning is 0.90 or more and 1.10 or less, and a ratio (FSINTERING / FBEFORE) between the maximum value FBEFORE and a maximum value FSINTERING of the frequency of a pore diameter of 2 nm or less determined from a pore distribution curve by a nitrogen gas adsorption method in silica particles after sintering at 600°C is 5 or more and 20 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to silica particles and a method for producing the same. [Background technology]

[0002] Silica particles are used as an additive or main component in toners, cosmetics, rubbers, abrasives, etc., and play roles such as improving the strength of resins, improving the fluidity of powders, suppressing packing, etc. The properties of silica particles are thought to depend on the shape and surface properties of the silica particles, and surface treatment of silica particles and compounding silica with metals or metal compounds have been proposed.

[0003] For example, Patent Document 1 discloses a toner having toner particles containing a binder resin and a colorant, and an external additive A, the external additive A having (i) a charge control agent present on the surface, (ii) a wall friction angle θ calculated from formula (1): θ = τ / 5.0 is 25.0° or less, where τ represents the shear stress obtained when a circular disk is rotated at (π / 10) rad / min by (π / 36) rad while entering a powder layer of the external additive A formed by applying a vertical load of 15.0 kPa with a vertical load of 5.0 kPa, (iii) a number-average particle size (D1) of the primary particles is 70 nm or more and 500 nm or less, and (iv) a density represented by formula (2): "density = area of ​​external additive A / area of ​​region surrounded by the envelope of external additive A" is 0.40 or more and 0.90 or less.

[0004] Furthermore, Patent Document 2 discloses "silica powder containing a plurality of silica particles in which a quaternary ammonium salt is introduced into a silica structure having an "Si-O" bond as a repeating unit."

[0005] Patent Document 3 discloses "a spherical silica composition comprising a silane coupling agent, a charge control agent, and spherical silica fine powder, the spherical silica fine powder having an average particle diameter of 0.090 μm or more and 0.140 μm or less as measured by a laser diffraction scattering type particle size distribution measuring device, a particle content of 0.150 μm or more being 5.0 mass% or more and 25.0 mass% or less, and a particle content of 0.300 μm or more being 1.0 mass% or less."

[0006] In addition, Patent Document 4 describes an electrostatic image developing toner comprising a mixture of toner particles and external charge control particles, which are used for controlling the triboelectric charge of the toner particles and are formed by applying a charge control agent (CCA) to the surface of transport particles having an average particle size of 20 to 500 nm, and are used for controlling the triboelectric charge of the toner particles. The external charge control particles are external charge control particles for controlling the triboelectric charge of the electrostatic image developing toner, which are formed by applying a charge control agent to the surface of transport particles and hydrophobic spherical silica fine particles having an average particle size of 20 to 500 nm obtained by hydrophobizing the surface of hydrophilic spherical silica fine particles obtained by a sol-gel method, and the charge control agent applied to the surface of the transport particles. The charge control agent (CCA) is added in an amount of 1×10 to 1 part by mass of the transport particles. -3 ~1×10 -1 parts by mass range, and the external charge control particles are mixed in an amount of 0.001 to 0.05 parts by mass per part by mass of the toner particles. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2018-045233 A [Patent Document 2] JP 2017-039618 A [Patent Document 3] JP 2015-000830 A [Patent Document 4] JP 2011-185998 A Summary of the Invention [Problem to be solved by the invention]

[0008] The object of the present invention is to provide silica particles containing a quaternary ammonium salt, The maximum frequency of pores with diameters of 2 nm or less obtained from the pore distribution curve of the nitrogen gas adsorption method for silica particles before cleaning, F BEFORE and the maximum frequency of pores with diameters of 2 nm or less, calculated from the pore distribution curve of the nitrogen gas adsorption method for the silica particles after washing. AFTER The ratio of (F BEFORE / F AFTER ) is less than 0.90, The maximum value F BEFORE and the maximum frequency F of pores with diameters of 2 nm or less obtained from the pore distribution curve of the silica particles after baking at 600 ° C. using the nitrogen gas adsorption method. SINTERING The ratio of (F SINTERING / F BEFORE ) is less than 5, Or, Resin particles with silica particles attached to their surfaces before cleaning are mixed with ferrite powder under specific conditions to form a mixture, and then the capacitance C of the resin particles with silica particles attached to their surfaces separated from the mixture is measured. BEFORE The resin particles having the washed silica particles attached to their surfaces and the ferrite powder are mixed under specific conditions to form a mixture, and then the capacitance C of the resin particles having the silica particles attached to their surfaces separated from the mixture is measured. AFTER The ratio of (C AFTER / C BEFORE ) is greater than 1.5, The object of the present invention is to provide silica particles in which an increase in electrostatic capacitance is suppressed as compared with that of the conventional silica particles. [Means for solving the problem]

[0009] Specific means for solving the above problems include the following aspects. <1> Contains quaternary ammonium salts, The maximum frequency of pores with diameters of 2 nm or less obtained from the pore distribution curve of the nitrogen gas adsorption method for silica particles before cleaning, F BEFOREand the maximum frequency of pores with diameters of 2 nm or less, calculated from the pore distribution curve of the nitrogen gas adsorption method for the silica particles after washing. AFTER The ratio of (F BEFORE / F AFTER ) is 0.90 or more and 1.10 or less, and, The maximum value F BEFORE and the maximum frequency F of pores with diameters of 2 nm or less obtained from the pore distribution curve of the silica particles after baking at 600 ° C. using the nitrogen gas adsorption method. SINTERING The ratio of (F SINTERING / F BEFORE ) is between 5 and 20, Silica particles. <2> Contains a quaternary ammonium salt, Resin particles with silica particles attached to their surfaces before cleaning are mixed with ferrite powder under specific conditions to form a mixture, and then the capacitance C of the resin particles with silica particles attached to their surfaces separated from the mixture is measured. BEFORE and, The resin particles with the washed silica particles attached to their surfaces are mixed with ferrite powder under specific conditions to form a mixture, and then the capacitance C of the resin particles with the silica particles attached to their surfaces separated from the mixture is measured. AFTER and, Ratio of (C AFTER / C BEFORE ) is 1.5 or less. <3> The quaternary ammonium salt includes a compound represented by the following general formula (AM): <1> or <2> The silica particles according to claim 1. [ka] (In the general formula (AM), R 1 , R 2 , R 3 and R 4 each independently represents an alkyl group, an aralkyl group, or an aryl group which may have a substituent; X - represents an anion. In general formula (AM), R 1 , R 2 , R 3 and R 4Two or more of may be linked together to form a ring.) <4> In the compound represented by the general formula (AM), R 1 , R 2 , R 3 and R 4 each independently represents an alkyl group having 1 to 16 carbon atoms or an aralkyl group having 7 to 10 carbon atoms, which may have a substituent; <3> The silica particles according to claim 1. <5> The number average particle diameter is 5 nm or more and 300 nm or less. <1> ~ <4> 13. Silica particles according to any one of claims 1 to 12. <6> The number average particle size is 5 nm or more and 100 nm or less. <5> The silica particles according to claim 1. <7> The ratio of the amount of nitrogen element N derived from the quaternary ammonium salt detected by oxygen / nitrogen analysis (N / silica particles x 100) is 0.01 or more and 1.0 or less, <1> ~ <6> 13. Silica particles according to any one of claims 1 to 12. <8> The average pore diameter is 0.55 nm or more and 2.00 nm or less. <1> ~ <7> 13. Silica particles according to any one of claims 1 to 12. <9> The particles are hydrophobically treated. <1> ~ <8> 13. Silica particles according to any one of claims 1 to 12. <10> A preparation step of preparing a suspension containing silica particles; a first surface treatment step of mixing the suspension with a quaternary ammonium salt and using a supercritical fluid to obtain a powder in which the silica particles are surface-treated with the quaternary ammonium salt; A method for producing silica particles, comprising the steps of: <11> After the first surface treatment step, The method further comprises a second surface treatment step of surface-treating the powder with an organosilicon compound in a supercritical fluid. <10> The method for producing silica particles according to claim 1. <12> Silica particles before cleaning are baked at 600℃, The volume V1 of micropores with a pore diameter of 2 nm or less calculated from the pore distribution curve of the nitrogen gas adsorption method is 0.05 cm 3 / g or more 0.80cm 3 / g or less, When the mesopore volume having a pore diameter of more than 2 nm and not more than 50 nm obtained from a pore distribution curve of a nitrogen gas adsorption method is defined as V2, the ratio of V2 to V1 (V2 / V1) is 2 or more and 10 or less. <1> The silica particles according to claim 1. <13> The number average particle size is 30 nm or more and 100 nm or less, and the average circularity is 0.65 or more and 0.90 or less. <12> The silica particles according to claim 1. <14> The number average particle size is 30 nm or more and 70 nm or less, and the average circularity is 0.75 or more and 0.88 or less. <13> The silica particles according to claim 1. <15> The micropore volume V1 is 0.10 cm 3 / g or more 0.50cm 3 / g or less <12> ~ <14> 13. Silica particles according to any one of claims 1 to 12. <16> The ratio of V2 to V1 (V2 / V1) is 2 or more and 5 or less. <12> ~ <15> 13. Silica particles according to any one of claims 1 to 12. <17> The quaternary ammonium salt includes a compound represented by the following general formula (AM): <12> ~ <16> 13. Silica particles according to any one of claims 1 to 12. [ka] (In the general formula (AM), R 1 , R 2 , R 3 and R 4 each independently represents an alkyl group, an aralkyl group, or an aryl group which may have a substituent; X - represents an anion. In general formula (AM), R 1 , R 2 , R 3 and R 4 Two or more of may be linked together to form a ring.) <18> The silica particles are sol-gel silica particles. <12> ~ <17> 13. Silica particles according to any one of claims 1 to 12. Effect of the Invention

[0010] <1> , <3> , <4> , <5> , <6> or <9> According to the invention, The maximum frequency of pores with diameters of 2 nm or less obtained from the pore distribution curve of the nitrogen gas adsorption method for silica particles before cleaning, F BEFORE and the maximum frequency of pores with diameters of 2 nm or less, calculated from the pore distribution curve of the nitrogen gas adsorption method for the silica particles after washing. AFTER The ratio of (F BEFORE / F AFTER ) is less than 0.90, or The maximum value F BEFORE and the maximum frequency F of pores with diameters of 2 nm or less obtained from the pore distribution curve of the silica particles after baking at 600 ° C. using the nitrogen gas adsorption method. SINTERING The ratio of (F BEFORE / F SINTERING ) is less than 5, Silica particles are provided in which an increase in capacitance is suppressed.

[0011] <2> , <3> , <4> , <5> , <6> or <9> According to the invention, Resin particles with silica particles attached to their surfaces before cleaning are mixed with ferrite powder under specific conditions to form a mixture, and then the capacitance C of the resin particles with silica particles attached to their surfaces separated from the mixture is measured. BEFORE The resin particles having the washed silica particles attached to their surfaces and the ferrite powder are mixed under specific conditions to form a mixture, and then the capacitance C of the resin particles having the silica particles attached to their surfaces separated from the mixture is measured. AFTER The ratio of (C AFTER / C BEFORE ) is greater than 1.5, Silica particles are provided in which an increase in capacitance is suppressed.

[0012] <7> According to the invention, The silica particles provided have a suppressed increase in capacitance compared to when the ratio of the amount of nitrogen element N derived from quaternary ammonium salts detected by an oxygen / nitrogen analyzer (N / silica particles x 100) is less than 0.01% or exceeds 1.0%.

[0013] <8> According to the invention, The silica particles provided have a suppressed increase in capacitance compared to when the average pore diameter is less than 0.55 nm or exceeds 2.00 nm.

[0014] <10> or <11> According to the invention, A method for producing silica particles is provided in which an increase in capacitance is suppressed compared to a production method not including the first surface treatment step.

[0015] <12> ~ <18> According to the present invention, silica particles before cleaning are calcined at 600° C., and then The volume V1 of micropores with a pore diameter of 2 nm or less calculated from the pore distribution curve of the nitrogen gas adsorption method is 0.05 cm 3 / g or less than 0.80cm 3 / g or more of silica particles; The micropore volume V1 is 0.05 cm 3 / g or more 0.80cm 3 / g or less, and when V2 is the mesopore volume having a pore diameter of more than 2 nm and not more than 50 nm obtained from a pore distribution curve obtained by a nitrogen gas adsorption method, the increase in capacitance is suppressed compared to silica particles in which the ratio of V2 to V1 (V2 / V1) is less than 2 or exceeds 10. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, embodiments of the present invention will be described. These descriptions and examples are merely illustrative of the embodiments, and are not intended to limit the scope of the embodiments.

[0017] In the numerical ranges described in this specification, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in another stepwise manner. In addition, in the numerical ranges described in this disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples.

[0018] In this specification, each component may contain multiple corresponding substances. In this specification, when referring to the amount of each component in a composition, if multiple substances corresponding to each component are present in the composition, the amount refers to the total amount of those multiple substances present in the composition, unless otherwise specified.

[0019] <Silica particles> The silica particles according to the first embodiment contain a quaternary ammonium salt, and the maximum frequency F of pores having a diameter of 2 nm or less is determined from a pore distribution curve of the silica particles before washing using a nitrogen gas adsorption method. BEFORE and the maximum frequency of pores with diameters of 2 nm or less, calculated from the pore distribution curve of the nitrogen gas adsorption method for the silica particles after washing. AFTER The ratio of (F BEFORE / F AFTER ) is 0.90 or more and 1.10 or less, and the maximum value F BEFORE and the maximum frequency F of pores with diameters of 2 nm or less obtained from the pore distribution curve of the silica particles after baking at 600 ° C. using the nitrogen gas adsorption method. SINTERING The ratio of (F SINTERING / F BEFORE ) is between 5 and 20 inclusive.

[0020] The silica particles according to the second embodiment contain a quaternary ammonium salt, and are prepared by mixing resin particles having unwashed silica particles attached to their surfaces with ferrite powder under specific conditions to obtain a mixture, and then the silica particles separated from the mixture are subjected to a measurement of the capacitance C of the resin particles having the silica particles attached to their surfaces. BEFORE The resin particles having the washed silica particles attached to their surfaces and the ferrite powder are mixed under specific conditions to prepare a mixture, and then the capacitance C of the resin particles having the silica particles attached to their surfaces separated from the mixture is AFTER The ratio of (C AFTER / C BEFORE ) is less than or equal to 1.5.

[0021] Hereinafter, the silica particles according to the first embodiment and the silica particles according to the second embodiment will be collectively referred to as the silica particles according to this embodiment.

[0022] Silica particles are used in various applications such as fillers and external additives. However, conventional silica particles tend to have high electrostatic capacitance on the particle surface. Therefore, the electrical resistance of the contact material that comes into contact with the silica particles or the mixture in which the silica particles and the contact material are mixed tends to increase, that is, static electricity tends to accumulate.

[0023] On the other hand, the silica particles according to the present embodiment have the above-mentioned structure, and therefore the increase in capacitance is suppressed. Although the reason for this is not entirely clear, it is presumed to be as follows.

[0024] The silica particles according to the present embodiment contain a quaternary ammonium salt. The quaternary ammonium salt has a positive charge, and the silica particles containing this quaternary ammonium salt tend to be less likely to be triboelectrically charged as a whole bulk than silica particles not containing a quaternary ammonium salt because the particle surface has a charge of the opposite polarity to the silica surface.

[0025] Furthermore, the silica particles according to the first embodiment have a ratio of the maximum frequency of pores with diameters of 2 nm or less, determined from a pore distribution curve by a nitrogen gas adsorption method, before and after washing (F BEFORE / F AFTER ) is 0.90 or more and 1.10 or less, and the ratio of the maximum frequency of the pores having a diameter of 2 nm or less in the silica particles before and after the calcination (F SINTERING / F BEFORE ) is 5 or more and 20 or less. In other words, the particles before calcination have no pores because the quaternary ammonium salt exists inside the pores, but when the quaternary ammonium salt is removed by the calcination process, pores exist on the silica surface. Since the quaternary ammonium salt exists inside the pores, the quaternary ammonium salt contained in the silica particles tends not to be released from the surface even after washing. As a result, it is considered that the increase in the electrostatic capacitance on the particle surface of the silica particles is suppressed.

[0026] On the other hand, for the silica particles according to the second embodiment, the resin particles having silica particles attached to their surfaces and the ferrite powder are mixed and separated under the above conditions, and the capacitance ratio (CAFTER / C BEFORE ) is 1.5 or less. In other words, even after the resin particles having silica particles attached to their surfaces are brought into contact with the ferrite powder, they are less likely to be triboelectrically charged with the ferrite powder, that is, they tend to be less likely to accumulate static electricity. As a result, it is believed that the increase in the electrostatic capacitance on the particle surfaces of the silica particles is suppressed.

[0027] [Properties of silica particles] Maximum frequency calculated from the pore size distribution curve of the nitrogen gas adsorption method The silica particles according to the first embodiment are determined from a pore distribution curve of the silica particles before washing by a nitrogen gas adsorption method to have a maximum frequency F of pores having a diameter of 2 nm or less. BEFORE and the maximum frequency of pores with diameters of 2 nm or less, calculated from the pore distribution curve of the nitrogen gas adsorption method for the silica particles after washing. AFTER The ratio of (F BEFORE / F AFTER ) is 0.90 or more and 1.10 or less, and from the viewpoint of further suppressing the increase in capacitance, it is preferably 0.97 or more and 1.15 or less, and more preferably 0.95 or more and 1.1 or less.

[0028] The silica particles according to the second embodiment have a maximum frequency F of pores with diameters of 2 nm or less obtained from a pore distribution curve of the silica particles before washing using a nitrogen gas adsorption method. BEFORE and the maximum frequency of pores with diameters of 2 nm or less, calculated from the pore distribution curve of the nitrogen gas adsorption method for the silica particles after washing. AFTER The ratio of (F BEFORE / F AFTER From the viewpoint of further suppressing an increase in capacitance, it is preferably 0.90 or more and 1.10 or less, more preferably 0.97 or more and 1.15 or less, and even more preferably 0.95 or more and 1.1 or less.

[0029] The ratio (F BEFORE / F AFTER ) within the above range is not particularly limited, but an example of such a method includes, in the production of silica particles, a method of surface-treating silica particles with a quaternary ammonium salt using a supercritical fluid.

[0030] The silica particles according to the first embodiment are determined from a pore distribution curve of the silica particles before washing by a nitrogen gas adsorption method to have a maximum frequency F of pores having a diameter of 2 nm or less. BEFORE and the maximum frequency F of pores with diameters of 2 nm or less obtained from the pore distribution curve of the silica particles after baking at 600 ° C. using the nitrogen gas adsorption method. SINTERING The ratio of (F SINTERING / F BEFORE ) is 5 or more and 20 or less, and from the viewpoint of further suppressing an increase in capacitance, it is preferably 5 or more and 15 or less, and more preferably 7 or more and 12 or less.

[0031] The silica particles according to the second embodiment have a maximum frequency F of pores with diameters of 2 nm or less obtained from a pore distribution curve by a nitrogen gas adsorption method. BEFORE and the maximum frequency F of pores with diameters of 2 nm or less obtained from the pore distribution curve of the silica particles after baking at 600 ° C. using the nitrogen gas adsorption method. SINTERING The ratio of (F SINTERING / F BEFORE ), from the viewpoint of further suppressing an increase in capacitance, it is preferably 5 or more and 20 or less, more preferably 5 or more and 15 or less, and even more preferably 7 or more and 12 or less.

[0032] The ratio before and after firing (F SINTERING / F BEFORE ) within the above range is not particularly limited, but an example of such a method includes, in the production of silica particles, a method of surface-treating silica particles with a quaternary ammonium salt using a supercritical fluid.

[0033] The pore size distribution curve for the nitrogen gas adsorption method is derived from various calculation formulas based on the adsorption isotherm obtained by measuring the amount of adsorbed nitrogen gas. First, the silica particles, which are the adsorbent, are cooled to liquid nitrogen temperature (-196°C), nitrogen gas is introduced, and the amount of adsorption is determined by a constant volume method or a gravimetric method. The pressure of the introduced nitrogen gas is gradually increased, and an adsorption isotherm is created by plotting the amount of adsorbed nitrogen gas for each equilibrium pressure. From this adsorption isotherm, a pore size distribution curve, with the vertical axis representing frequency and the horizontal axis representing pore diameter, is calculated using calculation formulas such as the MP method, HK method, SF method, and CY method. From the obtained pore size distribution curve, the maximum frequency when the pore diameter is 2 nm or less is determined.

[0034] Capacitance The silica particles according to the first embodiment are prepared by mixing resin particles having unwashed silica particles attached to their surfaces with ferrite powder under specific conditions to obtain a mixture, and then measuring the capacitance C of the resin particles having silica particles attached to their surfaces, which are separated from the mixture. BEFORE The resin particles having the washed silica particles attached to their surfaces and the ferrite powder are mixed under specific conditions to prepare a mixture, and then the capacitance C of the resin particles having the silica particles attached to their surfaces separated from the mixture is AFTER The ratio of (C AFTER / C BEFORE ) is preferably 1.5 or less, more preferably 1.3 or less, and even more preferably 1.1 or less, from the viewpoint of further suppressing an increase in capacitance.

[0035] The silica particles according to the second embodiment are prepared by mixing resin particles having silica particles before cleaning attached to their surfaces with ferrite powder under specific conditions to obtain a mixture, and then measuring the capacitance C of the resin particles having silica particles attached to their surfaces that are separated from the mixture. BEFORE The resin particles having the washed silica particles attached to their surfaces and the ferrite powder are mixed under specific conditions to prepare a mixture, and then the capacitance C of the resin particles having the silica particles attached to their surfaces separated from the mixture is AFTER The ratio of (C AFTER / C BEFORE) is 1.5 or less, and from the viewpoint of further suppressing an increase in capacitance, it is preferably 2.0 or less, and more preferably 2.5 or less.

[0036] The ratio (C AFTER / C BEFORE ) within the above range is not particularly limited, but an example of such a method includes, in the production of silica particles, a method of surface-treating silica particles with a quaternary ammonium salt using a supercritical fluid.

[0037] The resin particles are not particularly limited, but an acrylic resin (for example, MA1010 manufactured by Nippon Shokubai Co., Ltd.) was used. The ferrite powder used is soft ferrite (for example, KNI106GSM manufactured by JFE Chemical Corporation). The specific conditions refer to the following conditions: Mass ratio: Silica particles / resin particles = 2 / 100, silica-attached resin particles / ferrite powder = 1 / 10 ·Mixing temperature: Room temperature (10℃) Mixing equipment: Turbula shaker / mixer (e.g., T2F manufactured by Shinmaru Enterprises Co., Ltd.) ·Mixing time: 5 minutes ·Mixing speed: 49rpm

[0038] The capacitance is measured as follows. After stirring with the Turbula shaker mixer, 2 g of the sample is placed in a metal container lined with a 20 μm mesh stainless steel wire screen and measured with a charge measuring device (for example, TB-200 manufactured by Toshiba Chemical Co., Ltd.).

[0039] Micropore volume V1 and mesopore volume V2 The silica particles according to the first and second embodiments are prepared by calcining the silica particles before washing at 600° C., and then The volume V1 of micropores with a pore diameter of 2 nm or less calculated from the pore distribution curve of the nitrogen gas adsorption method is 0.05 cm 3 / g or more 0.80cm 3 / g or less, When the volume of mesopores having a pore diameter of more than 2 nm and not more than 50 nm obtained from a pore distribution curve by nitrogen gas adsorption is defined as V2, the ratio of V2 to V1 (V2 / V1) is preferably 2 or more and 10 or less.

[0040] When the micropore volume and mesopore volume of silica particles satisfy the above conditions, quaternary ammonium salt can penetrate more easily into the pores of silica particles. Therefore, even after washing, the quaternary ammonium salt contained in the silica particles tends to be less likely to be separated from the surface. As a result, the increase in the capacitance of the particle surface of the silica particles is more suppressed.

[0041] In surface treatment of silica particles with quaternary ammonium salt using a supercritical fluid, the quaternary ammonium salt can be penetrated into the pores of the silica particles, making it possible to prevent the detachment of the quaternary ammonium salt even when washed. However, if the micropore volume V1 and mesopore volume V2 of the silica particles satisfy the above conditions, the quaternary ammonium salt can easily penetrate into the mesopores and micropores of the silica particles even when the surface of the silica particles is treated with the quaternary ammonium salt by the spray drying method. This makes it difficult for the quaternary ammonium salt contained in the silica particles to be released even after washing. As a result, it is considered that the increase in the electrostatic capacitance on the particle surface of the silica particles is suppressed. In addition, it is preferable to use TP415 described in the Examples below as the quaternary ammonium salt used in the surface treatment of silica particles with a quaternary ammonium salt by the spray drying method.

[0042] Even in the case of surface treatment of silica particles with a quaternary ammonium salt by a spray drying method, in order to facilitate penetration of the quaternary ammonium salt into the mesopores and micropores of the silica particles, the micropore volume V1 is set to 0.10 cm 3 / g or more 0.50cm 3 It is more preferable that the molecular weight is not more than 1 / g.

[0043] Even in the case of surface treatment of silica particles with a quaternary ammonium salt by a spray drying method, it is more preferable that the ratio of V2 to V1 (V2 / V1) is 2 or more and 5 or less, from the viewpoint of making it easier for the quaternary ammonium salt to penetrate into the mesopores and micropores of the silica particles.

[0044] The micropore volume V1 and the mesopore volume V2 are measured as follows. An adsorption isotherm is created using the nitrogen gas adsorption method, and a pore size distribution curve, in which the vertical axis represents frequency and the horizontal axis represents pore diameter, is calculated from this adsorption isotherm using calculation formulas such as the MP method, HK method, SF method, and CY method. From the obtained pore size distribution curve, an integrated pore volume distribution, in which the vertical axis represents volume and the horizontal axis represents pore diameter, is calculated. From the obtained integrated pore volume distribution, the micropore volume V1 and mesopore volume V2 are calculated as follows: Micropore volume V1: The total volume of all pores with a pore diameter of 2 nm or less Mesopore volume V2: The total volume of all pores with a pore diameter between 2 nm and 50 nm

[0045] How to clean silica particles The silica particles are washed as follows. 1g of silica particles, 2.5g of ethanol, and 2.5g of ion-exchanged water are placed in a 20ml lab screw tube, and mixed in an ultrasonic cleaner (e.g., Honda Electronics Co., Ltd., tabletop ultrasonic cleaner W-113, vibration frequency 45Hz) to obtain a mixture. The mixture is then centrifuged at 10,000rpm for 30 minutes in a centrifuge (e.g., KURABO Co., Ltd., FB-4000), the supernatant is discarded, and the precipitated silica particles are taken out. This process is repeated twice, and the silica particles are dried. This is the silica particles after washing.

[0046] ·Silica particle calcination method The silica particles are fired as follows. 1 g of silica particles is placed in a 20 ml crucible for firing, and the silica particles are fired using a firing machine (e.g., KM-100 manufactured by Advantec Toyo Co., Ltd.) under conditions of a nitrogen atmosphere at 600°C for 1 hour, and the resulting fired product is used as fired silica particles.

[0047] The ratio of the amount of nitrogen present (N / Si) In the silica particles of this embodiment, the ratio of the amount of nitrogen element N derived from the quaternary ammonium salt detected by oxygen / nitrogen analysis (N / silica particle x 100) is preferably 0.01% or more, more preferably 0.02% or more and 1.00% or less, and even more preferably 0.03% or more and 0.80% or less, from the viewpoint of further suppressing an increase in capacitance.

[0048] There are no particular limitations on the specific method for setting the ratio (N / silica particles x 100) within the above range, but examples include a method for adjusting the ratio and time for mixing a suspension containing silica particles with a quaternary ammonium salt in the production of silica particles.

[0049] Oxygen and nitrogen analysis is performed using an oxygen and nitrogen analyzer (e.g., EMGA-920 manufactured by Horiba, Ltd.) with an accumulation time of 45 seconds to obtain the proportion of the amount of nitrogen element present N (N / total particles × 100). If a material containing nitrogen element such as ammonia is used as a catalyst in the particle manufacturing process, a gas chromatograph mass spectrometer (e.g., GCMS-TQ8040NX manufactured by Shimadzu Corporation) is used to obtain the proportion of the amount of nitrogen element present N (N / total particles × 100) of the nitrogen-containing material used in the manufacturing process from the calibration curve of a known material, and the difference is used to obtain the amount of nitrogen element present derived from the quaternary ammonium salt.

[0050] In order to further suppress an increase in capacitance, the silica particles according to this embodiment preferably have an average pore diameter of 0.55 nm or more and 2.00 nm or less, more preferably 0.55 nm or more and 1.50 nm or less, and even more preferably 0.55 nm or more and 1.00 nm or less.

[0051] The average pore size of silica particles is calculated using various calculation formulas from the adsorption isotherm obtained by measuring the amount of nitrogen gas adsorbed. First, the silica particles, which are the adsorbent, are cooled to liquid nitrogen temperature (-196°C), nitrogen gas is introduced, and the amount of adsorption is determined by the constant volume method or gravimetric method. The pressure of the introduced nitrogen gas is gradually increased, and an adsorption isotherm is created by plotting the amount of nitrogen gas adsorbed for each equilibrium pressure. From this adsorption isotherm, the average pore size is calculated using calculation formulas such as the MP method, HK method, SF method, and CY method. Nitrogen gas adsorption measurement is performed under liquid nitrogen (77.4 K) using a high-precision gas adsorption amount measuring device (for example, BELSORP MAX II by MicrotrackBell) and ultra-high purity nitrogen gas.

[0052] The specific method for adjusting the average pore diameter in the silica particles to fall within the above range is not particularly limited, but examples thereof include: 1) a method of adjusting the liquid composition during granulation; 2) a method of adjusting the dropping speed during particle granulation; and 3) a method of adjusting the drying temperature.

[0053] From the viewpoint of further suppressing an increase in capacitance, the number average particle diameter of the silica particles according to this embodiment is preferably 5 nm or more and 300 nm or less, more preferably 5 nm or more and 200 nm or less, and even more preferably 5 nm or more and 100 nm or less. In addition, the silica particles according to this embodiment are calcined at 600° C. before cleaning, and the micropore volume V1 of the pores having a diameter of 2 nm or less determined from the pore distribution curve of the nitrogen gas adsorption method is 0.05 cm 3 / g or more 0.80cm 3 / g or less, and when V2 is the mesopore volume having a pore diameter of more than 2 nm and not more than 50 nm obtained from a pore distribution curve by a nitrogen gas adsorption method, and the ratio of V2 to V1 (V2 / V1) is 2 or more and 10 or less, from the viewpoint of further suppressing an increase in capacitance, the average circularity is preferably 0.65 or more and 0.90 or less, more preferably 0.75 or more and 0.88 or less, and even more preferably 0.75 or more and 0.085 or less. Here, the average circularity is the cumulative circularity of 50% from the smallest side in the distribution of circularities.

[0054] Furthermore, the silica particles according to this embodiment are calcined at 600° C. before cleaning, and the micropore volume V1 of the pores having a diameter of 2 nm or less determined from the pore distribution curve of the nitrogen gas adsorption method is 0.05 cm 3 / g or more 0.80cm 3 / g or less, and when V2 is the mesopore volume having a pore diameter of more than 2 nm and not more than 50 nm obtained from a pore distribution curve by a nitrogen gas adsorption method, and the ratio of V2 to V1 (V2 / V1) is 2 or more and 10 or less, from the viewpoint of further suppressing an increase in capacitance, the average circularity is preferably a number average particle diameter of 30 nm or more and 100 nm or less and an average circularity of 0.65 or more and 0.90 or less, and more preferably a number average particle diameter of 30 nm or more and 70 nm or less and an average circularity of 0.75 or more and 0.88 or less.

[0055] The number average particle size and average circularity of the silica particles are determined as follows. Silica particles are photographed using a scanning electron microscope (SEM), and the equivalent circle diameter (nm) of 100 randomly selected primary particles is determined by image analysis. The equivalent circle diameter of the cumulative 50% (50th particle) from the small diameter side in the distribution of equivalent circle diameters is taken as the number average particle diameter. The average circularity is taken as the cumulative 50% (50th particle) from the small diameter side in the distribution of circularity.

[0056] From the viewpoint of further suppressing an increase in capacitance, the silica particles according to this embodiment are preferably particles that have been subjected to a hydrophobization treatment.

[0057] [Silica particle material] (Quaternary ammonium salts) The silica particles according to this embodiment contain a quaternary ammonium salt. The quaternary ammonium salts may be used alone or in combination of two or more kinds. The quaternary ammonium salt is not particularly limited, and any known quaternary ammonium salt can be used.

[0058] From the viewpoint of further suppressing an increase in capacitance, the quaternary ammonium salt preferably contains a compound represented by general formula (AM). The compound represented by general formula (AM) may be used alone or in combination of two or more kinds.

[0059] [ka] In the general formula (AM), R 1 , R 2 , R 3 and R 4 each independently represents an alkyl group, an aralkyl group, or an aryl group which may have a substituent; X - represents an anion.

[0060] R 1 ~R 4 Examples of the alkyl group represented by the formula (I) include linear alkyl groups having 1 to 20 carbon atoms and branched alkyl groups having 3 to 20 carbon atoms. Examples of the linear alkyl group having 1 to 20 carbon atoms include a methyl group, an ethyl group, an n-propyl group, an n-butyl group, an n-pentyl group, an n-hexyl group, an n-heptyl group, an n-octyl group, an n-nonyl group, an n-decyl group, an n-undecyl group, an n-dodecyl group, an n-tridecyl group, an n-tetradecyl group, an n-pentadecyl group, and an n-hexadecyl group. Examples of the branched alkyl group having 3 to 20 carbon atoms include an isopropyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an isopentyl group, a neopentyl group, a tert-pentyl group, an isohexyl group, a sec-hexyl group, a tert-hexyl group, an isoheptyl group, a sec-heptyl group, a tert-heptyl group, an isooctyl group, a sec-octyl group, a tert-octyl group, an isononyl group, a sec-nonyl group, a tert-nonyl group, an isodecyl group, a sec-decyl group, and a tert-decyl group. Among the above, R 1 ~R 4The alkyl group represented by the formula (I) is preferably an alkyl group having 1 to 15 carbon atoms, such as a methyl group, an ethyl group, a butyl group, or a tetradecyl group.

[0061] R 1 ~R 4 Examples of the aralkyl group represented by the formula (I) include aralkyl groups having 7 to 30 carbon atoms. Examples of the aralkyl group having 7 to 30 carbon atoms include a benzyl group, a phenylethyl group, a phenylpropyl group, a 4-phenylbutyl group, a phenylpentyl group, a phenylhexyl group, a phenylheptyl group, a phenyloctyl group, a phenylnonyl group, a naphthylmethyl group, a naphthylethyl group, an anthracylmethyl group, and a phenyl-cyclopentylmethyl group. Among the above, R 1 ~R 4 The aralkyl group represented by the formula (I) is preferably an aralkyl group having 7 to 15 carbon atoms, such as a benzyl group, a phenylethyl group, a phenylpropyl group, or a 4-phenylbutyl group.

[0062] R 1 ~R 4 Examples of the aryl group represented by the formula (I) include aryl groups having 6 to 20 carbon atoms. Examples of the aryl group having 6 to 20 carbon atoms include a phenyl group, a pyridyl group, a naphthyl group, and the like. Among the above, R 1 ~R 4 The aryl group represented by the following formula (I) is preferably an aryl group having 6 to 10 carbon atoms, such as a phenyl group.

[0063] X - The anion represented by the formula (I) includes organic anions and inorganic anions. Examples of the organic anion include a polyfluoroalkylsulfonate ion, a polyfluoroalkylcarboxylate ion, a tetraphenylborate ion, an aromatic carboxylate ion, and an aromatic sulfonate ion (such as a 1-naphthol-4-sulfonate ion). Inorganic anions include MoO4 2- , O.H. - , F - , Fe(CN) 6 3- , Cl - , Br - , NO 2 - , NO 3 - , CO 3 2- , P.O. 4 3- , S.O. 4 2- etc.

[0064] In the general formula (AM), R 1 , R 2 , R 3 and R 4 Two or more of R may be linked together to form a ring. 1 , R 2 , R 3 and R 4 Examples of the ring formed by linking two or more of the above to each other include an alicyclic ring having from 2 to 20 carbon atoms, and a heterocyclic amine having from 2 to 20 carbon atoms.

[0065] In the silica particles according to the present embodiment, in order to further suppress an increase in capacitance, R 1 , R 2 , R 3 and R 4 each independently represents an alkyl group having 1 to 16 carbon atoms or an aralkyl group having 7 to 10 carbon atoms, which may have a substituent.

[0066] X in the compound represented by the general formula (AM) - Examples of structures other than the above are shown below, but the present embodiment is not limited to these.

[0067] [ka]

[0068] [Application] The silica particles according to this embodiment can be used in various fields such as fillers, abrasives, toners, and cosmetics. In particular, by adding the silica particles according to this embodiment to tire rubber, the accumulation of static electricity in the tire is suppressed, and the adverse effects of electromagnetic noise on electronic devices can be prevented.

[0069] <Method for producing silica particles> The method for producing silica particles according to this embodiment includes, in this order, a preparation step of preparing a suspension containing silica particles, and a first surface treatment step of mixing the suspension with a quaternary ammonium salt to obtain a powder of the silica particles that has been surface-treated with the quaternary ammonium salt.

[0070] The method for producing silica particles according to the present embodiment includes a first surface treatment step. In the first surface treatment step, a quaternary ammonium salt is fixed on the surface of the silica particles. Therefore, the quaternary ammonium salt creates a charge opposite to that of the silica surface on the particle surface, making it difficult for the silica particles to be triboelectrically charged, and thus making it easy to produce silica particles with a suppressed increase in capacitance.

[0071] The steps of the manufacturing method according to this embodiment will be described in detail below.

[0072] [Preparation process] The method for producing silica particles according to this embodiment includes a preparation step. In the preparation step, a suspension containing silica particles is prepared.

[0073] The preparation process may include, for example, (i) preparing a silica particle suspension by mixing a solvent containing an alcohol with silica particles; (ii) A step of granulating silica particles by a sol-gel method to obtain a silica particle suspension etc. Examples of the silica particles used in (i) include sol-gel silica particles (silica particles obtained by a sol-gel method), aqueous colloidal silica particles, alcoholic silica particles, fumed silica particles obtained by a gas phase method, fused silica particles, and the like. The alcohol-containing solvent used in (i) may be a solvent of alcohol alone or a mixed solvent of alcohol and other solvents. Examples of alcohol include lower alcohols such as methanol, ethanol, n-propanol, isopropanol, and butanol. Examples of other solvents include water; ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; cellosolves such as methyl cellosolve, ethyl cellosolve, butyl cellosolve, and cellosolve acetate; and ethers such as dioxane and tetrahydrofuran. In the case of a mixed solvent, the proportion of alcohol is preferably 80% by mass or more, more preferably 90% by mass or more.

[0074] The step (1-a) is preferably a step of granulating silica particles by a sol-gel method to obtain a silica particle suspension. More specifically, step (1-a) may include, for example, An alkaline catalyst solution preparation step of preparing an alkaline catalyst solution containing an alkaline catalyst in a solvent containing alcohol; a silica particle producing step of producing silica particles by supplying tetraalkoxysilane and an alkali catalyst into an alkali catalyst solution; It is preferable that the method is a sol-gel method comprising the steps of:

[0075] The alkaline catalyst solution preparation step is preferably a step of preparing a solvent containing an alcohol and mixing the solvent with an alkaline catalyst to obtain an alkaline catalyst solution.

[0076] The solvent containing alcohol may be a solvent of alcohol alone or a mixed solvent of alcohol and other solvents. Examples of alcohol include lower alcohols such as methanol, ethanol, n-propanol, isopropanol, and butanol. Examples of other solvents include water; ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; cellosolves such as methyl cellosolve, ethyl cellosolve, butyl cellosolve, and cellosolve acetate; and ethers such as dioxane and tetrahydrofuran. In the case of a mixed solvent, the proportion of alcohol is preferably 80% by mass or more, more preferably 90% by mass or more.

[0077] The alkaline catalyst is a catalyst for promoting the reaction (hydrolysis reaction and condensation reaction) of tetraalkoxysilane. Examples of the alkaline catalyst include basic catalysts such as ammonia, urea, and monoamines, with ammonia being particularly preferred.

[0078] The concentration of the alkali catalyst in the alkali catalyst solution is preferably 0.5 mol / L or more and 1.0 mol / L or less, more preferably 0.6 mol / L or more and 0.8 mol / L or less, and still more preferably 0.65 mol / L or more and 0.75 mol / L or less, from the viewpoint of increasing the particle size uniformity and circularity of the produced silica particles.

[0079] The silica particle production step is a step in which tetraalkoxysilane and an alkali catalyst are separately supplied to an alkali catalyst solution, and the tetraalkoxysilane is reacted (hydrolysis reaction and condensation reaction) in the alkali catalyst solution to produce silica particles.

[0080] In the silica particle production process, core particles are produced by the reaction of tetraalkoxysilane in the initial stage of supplying tetraalkoxysilane (core particle production stage), and then these core particles grow (core particle growth stage) to produce silica particles.

[0081] Examples of tetraalkoxysilanes include tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, tetrabutoxysilane, etc. From the viewpoint of controllability of the reaction rate or uniformity of the shape of the produced silica particles, tetramethoxysilane or tetraethoxysilane is preferred.

[0082] Examples of the alkali catalyst to be supplied to the alkali catalyst solution include basic catalysts such as ammonia, urea, monoamines, and quaternary ammonium salts, with ammonia being particularly preferred. The alkali catalyst supplied together with the tetraalkoxysilane may be of the same type as the alkali catalyst already contained in the alkali catalyst solution, or may be of a different type, but is preferably of the same type.

[0083] The method for supplying the tetraalkoxysilane and the alkali catalyst into the alkali catalyst solution may be a method for supplying them continuously or intermittently.

[0084] In the silica particle production step, the temperature of the alkaline catalyst solution (the temperature at the time of supply) is preferably 5°C or more and 50°C or less, and more preferably 15°C or more and 40°C or less.

[0085] [First surface treatment process] The method for producing silica particles according to this embodiment includes a first surface treatment step. In the first surface treatment step, the suspension is mixed with a quaternary ammonium salt to obtain a powder in which the silica particles are surface-treated with the quaternary ammonium salt. When a process using a supercritical fluid is used in the first surface treatment process, the quaternary ammonium salt can easily penetrate into the pores of the silica particles, and silica particles can be obtained from which the quaternary ammonium salt contained in the silica particles is less likely to be released even when washed. On the other hand, after the silica particles before cleaning were baked at 600°C, the micropore volume V1 of pores with diameters of 2 nm or less calculated from the pore distribution curve of the nitrogen gas adsorption method was 0.05 cm 3 / g or more 0.80cm 3 / g or less, and where V2 is the mesopore volume having a pore diameter of more than 2 nm and not more than 50 nm obtained from a pore distribution curve by a nitrogen gas adsorption method, and the ratio of V2 to V1 (V2 / V1) is 2 or more and 10 or less, when silica particles are surface-treated with a quaternary ammonium salt, the quaternary ammonium salt can easily penetrate into the mesopores and micropores of the silica particles even by a spray drying method, and silica particles from which the quaternary ammonium salt contained in the silica particles is unlikely to be released even when washed can be obtained.

[0086] Preferred examples of the quaternary ammonium salt include those exemplified as the quaternary ammonium salt in the silica particles according to this embodiment.

[0087] The total amount of the quaternary ammonium salt is preferably 0.5 mass% or more, more preferably 1.5 mass% or more and 10 mass% or less, and even more preferably 2 mass% or more and 5 mass% or less, based on the solid content of the suspension containing silica particles.

[0088] The conditions for the surface treatment of the silica particles with a quaternary ammonium salt are not particularly limited, and for example, the surface treatment is carried out by reacting the quaternary ammonium salt with stirring at a temperature in the range of 20° C. or more and 50° C. or less.

[0089] The first surface treatment step is carried out, for example, by mixing a silica particle suspension with an alcoholic solution containing a quaternary ammonium salt in alcohol. It is also preferable to carry out the first surface treatment step by passing a supercritical fluid through the mixture. Therefore, the manufacturing method according to the present embodiment further includes a step of preparing an alcoholic solution containing a quaternary ammonium salt in alcohol, and it is preferable to carry out the step in advance.

[0090] The alcohol may be the same type as the alcohol contained in the silica particle suspension or may be a different type, but it is more preferable that the alcohol be the same type.

[0091] In an alcohol solution containing a quaternary ammonium salt in alcohol, the concentration of the quaternary ammonium salt is preferably from 0.05% by mass to 10% by mass, and more preferably from 0.1% by mass to 6% by mass.

[0092] Examples of substances used as supercritical fluids include carbon dioxide, water, methanol, ethanol, acetone, etc. The first surface treatment step is preferably a step using supercritical carbon dioxide from the viewpoints of treatment efficiency and suppression of generation of coarse particles.

[0093] Specifically, the first surface treatment step is carried out, for example, by the following operations. The suspension containing the silica particles and a quaternary ammonium salt are placed in a sealed reactor and mixed. Next, liquefied carbon dioxide is introduced into the sealed reactor, and the sealed reactor is heated and the pressure inside the sealed reactor is increased by a high-pressure pump, so that the carbon dioxide in the sealed reactor is in a supercritical state. Then, the liquefied carbon dioxide is flowed into the sealed reactor and the supercritical carbon dioxide is flowed out of the sealed reactor, so that the supercritical carbon dioxide is circulated through the suspension in the sealed reactor. While the supercritical carbon dioxide is flowing through the suspension, the solvent is dissolved in the supercritical carbon dioxide, and the solvent is removed along with the supercritical carbon dioxide flowing out of the sealed reactor. The temperature and pressure in the closed reactor are those that can make carbon dioxide supercritical, i.e., the critical point of carbon dioxide is 31.1°C / 7.38MPa, and the temperature and pressure are, for example, 40°C to 200°C and 10MPa to 30MPa.

[0094] The flow rate of the supercritical fluid in the first surface treatment step is preferably 80 mL / sec or more and 240 mL / sec or less.

[0095] [Second surface treatment process] The method for producing silica particles according to this embodiment may further include a second surface treatment step after the first surface treatment step. In the second surface treatment step, the silica particles that have been surface-treated with the quaternary ammonium salt are surface-treated with an organosilicon compound. By undergoing the second surface treatment step, the functional groups of the organosilicon compound react with the OH groups on the surface of the silica particles, and, for example, silica particles containing atomic groups of -Si-O-Si-R (R is an organic group) on the surface tend to be produced. The second surface treatment step may use a wet treatment or a supercritical treatment.

[0096] Specifically, the second surface treatment step by wet treatment is carried out, for example, by the following procedure: The silica particle suspension after the first surface treatment step is heated to 60° C. while being mixed with a stirrer, and an organosilicon compound is added to perform surface treatment. The stirring time is preferably 10 minutes to 24 hours, more preferably 20 minutes to 120 minutes, and even more preferably 20 minutes to 90 minutes.

[0097] Specifically, the second surface treatment step using supercritical treatment is carried out, for example, by the following procedure. It is believed that the use of a supercritical fluid improves the efficiency of the reaction between the organosilicon compound and the surface of the silica particles, resulting in a high level of surface treatment. Examples of substances used as supercritical fluids include carbon dioxide, water, methanol, ethanol, acetone, etc. The second surface treatment step is preferably a step using supercritical carbon dioxide from the viewpoints of treatment efficiency and suppression of generation of coarse particles.

[0098] Powders, i.e., silica particles surface-treated with a quaternary ammonium salt and an organosilicon compound, are placed in a closed reactor equipped with an agitator, and then liquefied carbon dioxide is introduced into the closed reactor, which is then heated and the pressure in the closed reactor is increased by a high-pressure pump to bring the carbon dioxide in the closed reactor into a supercritical state.Then, the agitator is operated to agitate the reaction system. The temperature and pressure in the closed reactor are set to those that put carbon dioxide into a supercritical state. The critical point of carbon dioxide is 31.1°C / 7.38MPa, and the temperature and pressure are, for example, 40°C to 200°C / 10MPa to 30MPa. The stirring time is preferably 10 minutes to 24 hours, more preferably 20 minutes to 120 minutes, and even more preferably 20 minutes to 90 minutes.

[0099] Examples of the organosilicon compound include: Silane compounds having a lower alkyl group, such as methyltrimethoxysilane, dimethyldimethoxysilane, trimethylchlorosilane, and trimethylmethoxysilane; Silane compounds having a vinyl group, such as vinyltrimethoxysilane and vinyltriethoxysilane; Silane compounds having an epoxy group, such as 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 3-glycidoxypropyltriethoxysilane; Silane compounds having a styryl group, such as p-styryltrimethoxysilane and p-styryltriethoxysilane; silane compounds having an aminoalkyl group, such as N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, and N-phenyl-3-aminopropyltrimethoxysilane; silane compounds having an isocyanato alkyl group, such as 3-isocyanatepropyltrimethoxysilane and 3-isocyanatepropyltriethoxysilane; Silazane compounds such as hexamethyldisilazane and tetramethyldisilazane; and the like.

[0100] [Solvent removal process] The method for producing silica composite particles according to this embodiment may further include a solvent removal step, if necessary. In the solvent removal step, the suspension containing the silica particles surface-treated with the quaternary ammonium salt is dried to remove the solvent to obtain a powder. Examples of the drying method include thermal drying, spray drying, and supercritical drying.

[0101] In thermal drying and spray drying, surface tension tends to act between particles at the end of drying, which can easily cause particle aggregation and the generation of coarse particles. However, by performing surface treatment with an organosilicon compound, it is possible to suppress the generation of coarse particles.

[0102] Spray drying can be performed by a conventional method using a commercially available spray dryer (disk rotation type, nozzle type, etc.). For example, spraying is performed by spraying the spray liquid into a hot air stream at a rate of 0.2 liters / hour to 1 liter / hour. In this case, the temperature of the hot air is preferably in the range of 70°C to 400°C at the inlet temperature and 40°C to 120°C at the outlet temperature. Here, if the inlet temperature is less than 70°C, the solids contained in the dispersion liquid are not sufficiently dried. If it exceeds 400°C, the shape of the particles will be distorted during spray drying. If the outlet temperature is less than 40°C, the solids are not dried to a sufficient degree and will adhere to the inside of the device. A more preferable inlet temperature is in the range of 100°C to 300°C. The silica particle concentration in the silica particle suspension during spray drying is preferably in the range of 10% by weight to 30% by weight in terms of solid content.

[0103] In supercritical drying, the solvent is removed by a supercritical fluid, so that the surface tension between particles is less likely to act, and the primary particles contained in the suspension are dried in a state in which aggregation is suppressed, making it easier to obtain silica particles with a highly uniform particle size and surface-treated with a quaternary ammonium salt.

[0104] Examples of substances used as supercritical fluids include carbon dioxide, water, methanol, ethanol, acetone, etc. From the viewpoints of processing efficiency and suppressing the generation of coarse particles, the solvent removal step is preferably a step using supercritical carbon dioxide.

[0105] Specifically, the solvent removal step is carried out, for example, by the following procedure. The suspension is placed in a sealed reactor, liquefied carbon dioxide is then introduced into the sealed reactor, the sealed reactor is heated, and the pressure inside the sealed reactor is increased by a high-pressure pump, so that the carbon dioxide in the sealed reactor is brought into a supercritical state. The liquefied carbon dioxide is then flowed into the sealed reactor, and the supercritical carbon dioxide is flowed out of the sealed reactor, so that the supercritical carbon dioxide is circulated through the suspension in the sealed reactor. While the supercritical carbon dioxide is flowing through the suspension, the solvent is dissolved in the supercritical carbon dioxide, and the solvent is removed along with the supercritical carbon dioxide flowing out of the sealed reactor. The temperature and pressure in the closed reactor are those that can make carbon dioxide supercritical, i.e., the critical point of carbon dioxide is 31.1°C / 7.38MPa, and the temperature and pressure are, for example, 40°C to 200°C and 10MPa to 30MPa.

[0106] The flow rate of the supercritical fluid in the solvent removal step is preferably 80 mL / sec or more and 240 mL / sec or less.

[0107] The obtained silica particles are preferably crushed or sieved as necessary to remove coarse particles and aggregates. Crushing is performed, for example, by a dry grinding device such as a jet mill, a vibration mill, a ball mill, or a pin mill. Sieving is performed, for example, by a vibration sieve or a wind sieving machine. EXAMPLES

[0108] Hereinafter, the embodiments of the present invention will be described in detail with reference to examples, but the embodiments of the present invention are not limited to these examples. In the following description, unless otherwise specified, all "%" is based on mass.

[0109] <Production of Silica Particles> [Examples 1 to 7] (preparation process) A suspension containing silica particles in each example was prepared as follows.

[0110] -Preparation of alkaline catalyst solution- In a glass reaction vessel equipped with a metal stirring rod, a dropping nozzle, and a thermometer, add the amounts of methanol, ion-exchanged water, and 10% ammonia water (NH 4 OH) was added and mixed with stirring to obtain an alkaline catalyst solution.

[0111] - Granulation of silica particles using the sol-gel method - The temperature of the alkaline catalyst solution was adjusted to 25°C, and the alkaline catalyst solution was replaced with nitrogen. Next, while stirring the alkaline catalyst solution, tetramethoxysilane (TMOS) and catalyst (NH 3 ) 4.4% ammonia water (NH 4 176 parts by mass of toluene and 176 parts by mass of hexane (OH) were added dropwise at the same time to obtain a silica particle suspension.

[0112] -Preparation of alcohol solution containing quaternary ammonium salt- An alcohol solution was prepared by diluting the type of quaternary ammonium salt shown in Table 1 with butanol.

[0113] (First surface treatment process) The temperature of the suspension of silica particles was adjusted to 25° C., and the alcohol liquid adjusted to 25° C. was added. At this time, the alcohol liquid was added so that the number of parts of the quaternary ammonium salt per 100 parts by mass of the solid content of the silica particle suspension was the amount shown in Table 1. Next, the mixture was stirred at 30° C. for 30 minutes to obtain a suspension containing silica particles containing a quaternary ammonium salt.

[0114] Next, 300 parts by mass of the suspension containing the silica particles containing the quaternary ammonium salt was placed in a reaction vessel, and CO 2 The temperature and pressure in the reactor were raised to 120°C / 20MPa. While maintaining the temperature and pressure, CO was added while stirring. 2The solvent was then removed over a period of 120 minutes to obtain a powder.

[0115] (Second surface treatment process) For every 100 parts by mass of powder remaining in the reaction vessel, 100 parts by mass of 1,1,1,3,3,3-hexamethyldisilazane (HMDS) was added. While stirring the materials, the reaction vessel was inflated with CO 2 The reactor was filled with 100% water and the temperature and pressure in the reactor were raised to 150°C / 15MPa. Stirring was continued for 30 minutes while maintaining the temperature and pressure. The pressure was then released to atmospheric pressure and cooled to room temperature (25°C). The stirrer was then stopped, and silica particles of each example were obtained as a powder.

[0116] [Example 8] Silica particles were produced in the same manner as in Example 1, except that the second surface treatment step was not performed.

[0117] [Example 9] (preparation process) -Preparation of alkaline catalyst solution- In a glass reaction vessel equipped with a metal stirring rod, a dropping nozzle, and a thermometer, add the amounts of methanol, ion-exchanged water, and 10% ammonia water (NH 4 OH) was added and mixed with stirring to obtain an alkaline catalyst solution.

[0118] - Granulation of silica particles using the sol-gel method - The temperature of the alkaline catalyst solution was adjusted to 45°C, and the alkaline catalyst solution was replaced with nitrogen. Next, while stirring the alkaline catalyst solution, tetramethoxysilane (TMOS) and catalyst (NH 3 ) 4.4% ammonia water (NH 4 At the same time, 186 parts by mass of toluene (OH) was added dropwise to prepare a silica particle suspension.

[0119] -Preparation of alcohol solution containing quaternary ammonium salt- An alcohol solution was prepared by diluting the type of quaternary ammonium salt shown in Table 1 with butanol.

[0120] -Quaternary ammonium salt treatment and surface treatment (first and second surface treatment steps)- The temperature of the suspension of silica particles was adjusted to 25° C., and the alcohol liquid adjusted to 25° C. was added. At this time, the alcohol liquid was added so that the number of parts of the quaternary ammonium salt per 100 parts by mass of the solid content of the silica particle suspension was the amount shown in Table 1. Next, the mixture was stirred at 30° C. for 30 minutes to obtain a suspension containing silica particles containing a quaternary ammonium salt. Next, the temperature of the suspension was adjusted to 55° C., and 100 parts by mass of 1,1,1,3,3,3-hexamethyldisilazane (HMDS) was added to 100 parts by mass of the powder. The material was surface-treated for 1 hour while being stirred, to obtain a suspension of silica particles.

[0121] (Solvent removal process) The solvent was removed from the suspension of silica particles using a Mini Spray Dryer B-290 (manufactured by Nippon Buchi Co., Ltd.). The input temperature in the cylinder was 200° C., the silica particle suspension was fed at a liquid feed rate of 0.2 L / hour, and the solvent was removed by spray drying to obtain dried silica particles.

[0122] [Comparative Example 1] Silica particles were produced in the same manner as in Example 1, except that the first surface treatment step did not involve surface treatment with a quaternary ammonium salt, that is, the following specifications were used.

[0123] The suspension of silica particles was placed in a reaction vessel at 300 parts by mass, and CO 2 The temperature and pressure in the reactor were raised to 120°C / 20MPa. While maintaining the temperature and pressure, CO was added while stirring. 2 Flow rate 5L / min / m 3 The solvent was then removed over 120 minutes to obtain a powder.

[0124] [Comparative Example 2] Silica particles were produced based on the production method described in Example 1 of JP 2017-39618 A.

[0125] [Table 1]

[0126] Table 2 shows the ratio of the maximum frequency of pores with diameters of 2 nm or less obtained from the pore distribution curve of the nitrogen gas adsorption method before and after cleaning for the silica particles of each example (F BEFORE / F AFTER ), the ratio of the maximum frequency of pores with diameters of 2 nm or less obtained from the pore distribution curve of the nitrogen gas adsorption method before and after firing (F SINTERING / F BEFORE ), the ratio of the capacitance of the silica particle-attached resin particles separated from the mixture obtained by mixing the silica particles and the ferrite powder under the above-mentioned conditions before and after washing (C AFTER / C BEFORE ), number average particle size, average pore size, and the ratio of the amount of nitrogen detected by oxygen and nitrogen analysis (N / silica particles × 100) are summarized. The measurement methods were as described above. In each table, "-" means that the corresponding material is not present.

[0127] Evaluation The silica particles of each example were evaluated for the increase in capacitance based on the following method and criteria, where G1 to G2 are acceptable. The evaluation method is as follows. The silica particles containing the prepared quaternary ammonium salt were added at 2 wt% to the surface of MA1010 manufactured by Nippon Shokubai, and 2g of this was mixed with 20g of KNI106GSM manufactured by JFE Chemical Co., Ltd. The mixed sample was stirred for 5 minutes using a turbulent shaker in a chamber with a humidity of 80% where charge does not easily accumulate, and the charge was measured. The result was CA1, the data for the charge measurement after stirring for 5 minutes using a turbulent shaker in a chamber with a humidity of 5% where charge is easily accumulated was CB1, and the data for the charge measurement after stirring for 60 minutes was CB2, and the ratios of these, CB1 / CA1 and CB2 / CB1, were used for evaluation.

[0128] G1: CB1 / CA2 is 1.0 or more and less than 1.15, and the increase in capacitance is strongly suppressed. G2: CB1 / CA2 is 1.15 or more and less than 1.3, and the increase in capacitance is suppressed. G3: CB1 / CA2 is 1.3 or more and less than 1.4, and the capacitance is slightly increased. G4: CB1 / CA2 is 1.4 or more, and capacitance is increased.

[0129] G1: CB2 / CB1 is 0.9 or more and less than 1.1, and the increase in capacitance is strongly suppressed. G2: CB2 / CB1 is 1.1 or more and less than 1.2, and the increase in capacitance is suppressed. G3: CB2 / CB1 is 1.2 or more and less than 1.3, and the capacitance is slightly increased. G4: CB2 / CB1 is 1.3 or more, and the capacitance is increased.

[0130] The abbreviations in each table refer to the following compounds. TMBAC: Benzyltributylammonium chloride ·TP-415:N,N-Dimethyl-N-tetradecyl-1-tetradecanaminium, hexa-μ-oxotetra-μ3-oxodi -μ5-oxotetradecaoxooctamolybdate(4-) (4:1) P-51: Benzyltrimethylammonium chloride

[0131] [Table 2]

[0132] As shown in Tables 1 and 2, it was found that the silica particles of the Examples suppressed the increase in capacitance compared to the silica particles of the Comparative Examples.

Claims

1. Contains a quaternary ammonium salt, The maximum frequency F of pores with diameters of 2 nm or less obtained from the pore distribution curve of the nitrogen gas adsorption method for silica particles before washing BEFORE and the maximum frequency F of pores with diameters of 2 nm or less obtained from the pore distribution curve of the silica particles after washing using a nitrogen gas adsorption method. AFTER and the ratio (F BEFORE / F AFTER ) is 0.90 or more and 1.10 or less, and, The maximum value F BEFORE and the maximum frequency F of pores with a diameter of 2 nm or less, which is obtained from the pore distribution curve of the silica particles after baking at 600° C. by the nitrogen gas adsorption method. SINTERING and the ratio (F SINTERING / F BEFORE ) is between 5 and 20 and The resin particles having silica particles attached to their surfaces before cleaning and the ferrite powder are mixed under specific conditions to prepare a mixture, and then the capacitance C of the resin particles having silica particles attached to their surfaces separated from the mixture is measured. BEFORE and, The resin particles with the washed silica particles attached to their surfaces are mixed with ferrite powder under specific conditions to prepare a mixture, and then the capacitance C of the resin particles with the silica particles attached to their surfaces separated from the mixture is measured. AFTER and, The ratio (C AFTER / C BEFORE ) is 1.5 or less.

2. The ratio (F BEFORE / F AFTER ) is 0.92 or more and 1.10 or less, The ratio (F SINTERING / F BEFORE ) is 6.2 or more and 19.2 or less, The ratio (C AFTER / C BEFORE 2. The method according to claim 1, wherein the sintering ratio is 1.41 or less. Rika particles.

3. The silica particles according to claim 1 or 2, wherein the quaternary ammonium salt comprises a compound represented by the following general formula (AM): 【Chemistry 1】 (In the general formula (AM), R 1 , R 2 , R 3 and R 4 each independently represents an alkyl group, an aralkyl group, or an aryl group which may have a substituent; X - represents an anion. In formula (AM), R 1 , R 2 , R 3 and R 4 Two or more of may be linked together to form a ring.

4. In the compound represented by the general formula (AM), R 1 , R 2 , R 3 and R 4 The silica particles according to claim 3 , wherein each independently represents an alkyl group having 1 to 16 carbon atoms or an aralkyl group having 7 to 10 carbon atoms, each of which may have a substituent.

5. The silica particles according to any one of claims 1 to 4, having a number average particle size of 5 nm or more and 300 nm or less.

6. The silica particles according to claim 5, having a number average particle size of 5 nm or more and 100 nm or less.

7. Any one of claims 1 to 6, wherein the ratio of the amount of nitrogen element N derived from the quaternary ammonium salt detected by oxygen / nitrogen analysis (N / silica particles×100) is 0.01 or more and 1.0 or less.

1. Silica particles according to claim 1.

8. Any one of claims 1 to 7, wherein the average pore diameter is 0.55 nm or more and 2.00 nm or less.

3. Silica particles according to claim 1.

9. The silica particles according to any one of claims 1 to 8, which are hydrophobically treated particles.

10. A preparation step of preparing a suspension containing silica particles; a first surface treatment step of mixing the suspension with a quaternary ammonium salt and using a supercritical fluid to obtain a powder in which the silica particles are surface-treated with the quaternary ammonium salt; in this order, Contains a quaternary ammonium salt, The maximum frequency F of pores with diameters of 2 nm or less obtained from the pore distribution curve of the nitrogen gas adsorption method for silica particles before washing BEFORE and the maximum frequency F of pores with diameters of 2 nm or less obtained from the pore distribution curve of the silica particles after washing using a nitrogen gas adsorption method. AFTER and the ratio (F BEFORE / F AFTER ) is 0.90 or more and 1.10 or less, and, The maximum value F BEFORE and the maximum frequency F of pores with a diameter of 2 nm or less, which is obtained from the pore distribution curve of the silica particles after baking at 600° C. by the nitrogen gas adsorption method. SINTERING and the ratio (F SINTERING / F BEFORE ) is between 5 and 20 and The silica particles before cleaning were calcined at 600°C, and then The volume V1 of micropores with a pore diameter of 2 nm or less calculated from the pore distribution curve of the nitrogen gas adsorption method is 0.05 cm 3 / g or more 0.80cm 3 / g or less, a ratio (V2 / V1) of V2 to V1, the ratio being 2 or more and 10 or less, wherein V2 is a mesopore volume having a pore diameter of more than 2 nm and not more than 50 nm, the ratio being 2 or more and 10 or less ...

11. The V1 is 0.05 cm 3 / g or more 0.11cm 3 / g or less, The method for producing silica particles according to claim 10, wherein the ratio (V2 / V1) is 2.2 or more and 3.0 or less.

12. After the first surface treatment step, The method for producing silica particles according to claim 10 or 11, further comprising a second surface treatment step of surface-treating the powder with an organosilicon compound in a supercritical fluid.

13. The silica particles before cleaning were calcined at 600°C, and then The volume V1 of micropores with a pore diameter of 2 nm or less calculated from the pore distribution curve of the nitrogen gas adsorption method is 0.05 cm 3 / g or more 0.80cm 3 / g or less, 2. The silica particles according to claim 1, wherein the ratio of V2 to V1 (V2 / V1) is 2 or more and 10 or less, when V2 is the volume of mesopores having a pore diameter of more than 2 nm and not more than 50 nm, as determined from a pore distribution curve by a nitrogen gas adsorption method.

14. 14. The silica particles according to claim 13, having a number average particle size of 30 nm or more and 100 nm or less and an average circularity of 0.65 or more and 0.90 or less.

15. 15. The silica particles according to claim 14, having a number average particle size of 30 nm or more and 70 nm or less and an average circularity of 0.75 or more and 0.88 or less.

16. The micropore volume V1 is 0.10 cm 3 / g or more 0.50cm 3 The silica particles according to any one of claims 13 to 15, wherein the silica particle size is 1 / g or less.

17. The silica particles according to any one of claims 13 to 16, wherein a ratio of V2 to V1 (V2 / V1) is 2 or more and 5 or less.

18. The silica particles according to any one of claims 13 to 17, wherein the quaternary ammonium salt comprises a compound represented by the following general formula (AM): 【Chemistry 2】 (In the general formula (AM), R 1 , R 2 , R 3 and R 4 each independently represents an alkyl group, an aralkyl group, or an aryl group which may have a substituent; X - represents an anion. In formula (AM), R 1 , R 2 , R 3 and R 4 Two or more of may be linked together to form a ring.

19. The silica particles according to any one of claims 13 to 18, which are sol-gel silica particles.

Citation Information

Patent Citations

  • Electrostatic image-developing toner and electric charge-controlling particle for external addition

    JP2011185998A

  • Spherical silica composition and use of the same

    JP2015000830A

  • Silica powder and positively-charged toner

    JP2017039618A

  • Toner and method for manufacturing toner

    JP2018045233A